El proyecto Tuning latinoamericano: la experiencia del área de Medicina - Hanne A., Christel (Revista Hospital Clínico Universidad de Chile, 2014)
Over the past decade, major changes in higher education have taken place worldwide. Thanks to a sustained reflexion within the European Community of Institutions of Higher Education, it has been possible to generate a common space where shared experiences and educational projects have been defined, respecting traditions and diversities. That’s how it was born and set the so-called European “Tuning Project” which was, later on, replicated in Latin America and other regions of the world.We understand the Tuning project as a network of learning communities; a network of academics and students, interconnected to discuss, strategize, share methodologies and compare results.One of the ultimate goals was to work in what was called the “meta profile” of the careers nvolved. In Latin America, it was possible to build a group of experts organized by disciplinary areas to work on this topic. Medicine was one of them.The aim of this paper is to show a summary of the work of the Latin American group in the area of Medicine.